Heterogeneity of peach rust disease progress within the tree canopy - Nesi, Cristiano N; Alves, Giselda; Ribeiro, Paulo Justiniano, Jr; May De Mio, Louise L (European journal of plant pathology, 2014)
Peach rust (Tranzschelia discolor) is a major foliar disease of peach that can cause severe defoliation. Few epidemiological studies have been conducted on peach rust, and there is no information concerning the spatial distribution of the disease within the canopy. This study aimed to characterise the onset and temporal progress of peach rust in three height strata in peach trees grown in two different orchards: one treated with fungicide and the second non-treated. Evaluations were conducted fortnightly between November and April for two consecutive years. Positional information for the disease within the canopy was obtained by assessing the incidence and severity of peach rust on leaves in both orchards. A linear mixed model with the position of shoots as the fixed effect and cultivars and blocks as random effects was adopted for the data analysis over both seasons, in the fungicide-treated orchard incidence and severity ranged from 60 to 90 % and 0.5 to 2 %, respectively, while in the non-treated orchard incidence and severity ranged from 90 to 100 % and 10 to 15 %, respectively. The area under the disease progress curve was greater for the upper shoots compared to the lower shoots, but the disease progress rates were similar. The logistic and exponential models best fitted the incidence and severity data, respectively. Urediniospores were detected by traps within the experimental area between late winter and early spring. Predominance of autoinfection or alloinfection is discussed.